The effects of Chinese Buddhist meditation tradition: the impact of nature observation and literary creation - Tiankai Liang; Minkai Sun; Minkai Sun; Seiko Goto (Frontiers in Psychology)
IntroductionAfter integrating with indigenous Chinese culture, Chinese Buddhist meditation traditions expanded beyond classical rock meditation to include new practices. This study examines the physiological and psychological effects of nature observation and literary creation within Chinese Buddhist meditation.MethodsExperiment 1 recruited 30 participants and used observation duration, heart rate, the Profile of Mood States (POMS), and a supplemental questionnaire to compare relaxation effects across water (LS), forest (FS), and rock (RS) landscapes at a Buddhist temple. Experiment 2 recruited 30 new participants and introduced a poetry-creation task in the most relaxing landscape (LS) to test additional effects.ResultsThe water LS significantly prolonged observation duration [LS: 379.835 ± 47.528 vs. FS: 210.656 ± 15.284 vs. RS: 272.157 ± 25.450, 95% CI (65.638, 272.719), p = 0.000, ηp2 = 0.443, 1-β = 0.985] and induced greater heart rate reduction (72.4 vs. 78.1 bpm at baseline, p = 0.001). POMS scores showed LS most improved negative moods (e.g., Depression-Dejection: −1.47 ± 0.38 vs. FS +1.07 ± 0.37, p < 0.001).ConclusionChinese Buddhist practices integrating water landscapes and poetry composition optimize relaxation (heart rate reduction: −7.3% in LS) and cognitive engagement, offering evidence-based insights for mental health interventions.